Infused virtue as virtue simply: the centrality of the Augustinian definition in Summa theologiae I/2.55–67. Issue 4 (6th December 2018) - Miner, Robert
Abstract: 'Virtue is a good quality of the mind, by which one lives rightly, which no one uses badly, which God works in us without us.' Thomas Aquinas quotes this 'Augustinian' definition near the beginning of his treatment of virtue in general. Because it fails to apply to acquired virtues, some conclude that Aquinas presents this definition only to set it aside. Against such interpretations, I demonstrate that Thomas' use of the definition is the key to understanding the treatment of virtue at Summa I/2.55–63. First, I show why Thomas places the definition where he does, at the end of question 55. Second, I show that the definition is not peripheral but rather discloses the inner logic of his treatment of virtue. Finally, I show that for the reader who grasps this inner logic, the conclusion drawn explicitly at Question 65 – that only infused virtue is virtue simply – is revealing but not surprising.